2020
DOI: 10.5114/aoms.2020.93343
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key pathways and genes in nonalcoholic fatty liver disease using bioinformatics analysis

Abstract: A b s t r a c t Introduction: Nonalcoholic fatty liver disease (NAFLD) is one of the most common types of liver disease in the world. However, the molecular mechanisms regulating the development of NAFLD have remained unclear. Material and methods: In the present study, we analyzed two public datasets (GSE48452 and GSE89632) to identify differentially expressed mRNAs in the progression of NAFLD. Next, we performed bioinformatics analysis to explore key pathways underlying NAFLD development. Results: Gene Ontol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
(35 reference statements)
5
18
0
Order By: Relevance
“…Interestingly, several studies applying bioinformatics analyses are in consistensy with our findings, revealing the possible implication of UBQLN4 [80], UBC [81] and PCNA [82] in NAFLD development as potential biomarkers. Likewise, a bioinformatics analysis in a PPI network of steatosis highlights CRK and MDM2 among of the top 10 important genes [83].…”
Section: Thsupporting
confidence: 84%
“…Interestingly, several studies applying bioinformatics analyses are in consistensy with our findings, revealing the possible implication of UBQLN4 [80], UBC [81] and PCNA [82] in NAFLD development as potential biomarkers. Likewise, a bioinformatics analysis in a PPI network of steatosis highlights CRK and MDM2 among of the top 10 important genes [83].…”
Section: Thsupporting
confidence: 84%
“…In humans, fructose consumption for ten weeks led to increased hepatic de novo lipogenesis and 23-hour postprandial hypertriglyceridemia [14], suggesting that fructose may contribute to the development of NAFLD via the circulating lipid pool [8]. These data are consistent with recent evidence indicating that transcriptomic changes accompanying the early development of NAFLD occur predominantly in hepatocytes [24]. To date, however, the impact of palmitate-and fructose-treated human hepatocytes on transcriptomic changes in HSCs has not yet been characterized.…”
Section: Introductionsupporting
confidence: 88%
“…A number of studies have investigated changes in intercellular metabolism resulting from exposure to these nutrients in primary or immortalized hepatocytes and hepatic stellate cells (HSCs) [20][21][22][23][24][25][26][27][28]. HSCs are quiescent under physiological conditions, but are activated to a myofibroblastic state in response to injurious stimuli, whereupon they begin to secrete cytokines and components of the extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…Primary cells have not been used to build cell models. In a bioinformatics analysis study on NAFLD, it is mentioned that the occurrence of NAFLD is also related to insulin signaling pathway, PPAR signaling pathway, p53 signaling pathway and mitogen-activated protein kinase (MAPK) signaling pathway ( Liu et al, 2020 ). The study found that giving p53 knockout mice a high-fat diet reduced the occurrence of NAFLD.…”
Section: Discussionmentioning
confidence: 99%